Risk factors for antenatal anxiety: a cross-sectional study in field antenatal clinics in Sri Lanka - Dulshika A Waas; Manathungei Nirmala Priyadarshanie; Sampatha Goonewardena; Aindralal Balasuriya; Chamara V Senaratna; Sharaine Fernando (BMJ Open)
Objectives We aimed to determine the prevalence and factors affecting antenatal anxiety (AA) among Sri Lankan women.Design We conducted a cross-sectional analysis of first trimester data from a population-based cohort of antenatal women.Setting Field antenatal clinics of four field health areas in Colombo District, Sri Lanka.Participants Antenatal women (n=535) in the first trimester of pregnancy and aged ≥18 years were sequentially recruited when they attended antenatal clinics selected using random cluster sampling. Those with hearing difficulty, visual and speaking problems or currently on treatment for mental disorders were excluded.Measures We used an interviewer-administered questionnaire to collect data. The AA was identified using the validated Sinhala version of Perinatal Anxiety Screening Scale (PASS-S). Self-reported demographic and pregnancy-related information were verified against health records. Psychosocial risk factors were self-reported. We investigated the associations between potential risk factors and AA using regression models that included confounders identified through a directed acyclic graph and reported using adjusted odds ratios (ORs) with 95% confidence intervals (CIs).Results The prevalence of AA during the first trimester of pregnancy, identified using a PASS threshold of ≥20, was 34.4% (n=184). We found several novel risk factors for AA, namely, physical (OR 2.1; 95% CI 1.4 to 3.2) and mental health problems of self (OR 2.3; 95% CI 1.2 to 4.4), physical (OR 2.1; 95% CI 1.4 to 3.4) and mental health problems of parents/spouse (OR 6.7; 95% CI 2.8 to 16.2), traumatic life situations (OR 2.7; 95% CI 1.5 to 4.8), substance abuse by the spouse (OR 3.5; 95% CI 1.9 to 6.6) and the spouse being away (OR 2.0; 95% CI 1.1 to 3.7). The other risk factors that we identified included domestic violence among family members (OR 6.4; 95% CI 1.3 to 31.0), loss of family support (OR 2.2; 95% CI 1.0 to 5.2), financial hardships (OR 1.7; 95% CI 1.0 to 2.8), accommodation-related issues (OR 2.2; 95% CI 1.0 to 4.9), unplanned pregnancy (OR 3.7; 95% CI 1.9 to 7.3), difficulties due to pregnancy (OR 2.0; 95% CI 1.1 to 3.4), changed or stopped education (OR 2.9; 95% CI 1.7 to 5.1), recent loss of employment (OR 2.9; 95% CI 1.2 to 7.0), recent death of a loved one (OR 3.5; 95% CI 2.0 to 5.9) and sleep problems during pregnancy (OR 1.6; 95% CI 1.1 to 2.3).Conclusions The prevalence of antenatal anxiety is high in Sri Lanka and is associated with several risk factors, not previously described, which are potentially modifiable.